A Recently Discovered Folia from the 12th-century Apostolus Christinopolitanus - Stanisław Wołoszczenko (Biblioteka)
One of the important Cyrillic medieval manuscripts from Kievan Rus is the Apostolus Christinopolitanus – a 12th-century codex which is now separated into two parts that are preserved (though some fragments have been lost) in Kyiv (Institute of Manuscript of V.I. Vernadskyi National Library of Ukraine, since 1927) and Lviv (History Museum of Lviv, since 1948). This article discusses four parchment folia from Kraków (The Princes Czartoryski Library, Poland) discovered in July 2020. Paleographical, orthographical, linguistic and textological features indicate that this section is the previously lost part of the Apostolus Christinopolitanus (excerpts from Act 13,5–20, 15,29–16,4, 1Tim 4,8–5,4 and 2Tim 1,10–2,4). The Kraków folia are the continuation of the Kyiv part and the beginning and final part of the Lviv part of the codex. The Kraków part was detached before 1888, when the manuscript was shown to the public at the Lviv Stauropegion Institute Exhibition and described and foliated for the catalogue by Antonij Petruševič. This article contains photocopies of all of the newly-discovered fragments.